THE RISE OF THE RADICAL RIGHT PARTIES: MAINSTREAMING AND NORMALIZATION OF ILLIBERAL VALUES IN DEMOCRATIC SOCIETIES - Krtolica, Marko (Polish Academy of Sciences - Scientific Centre in Vienna and University of Warsaw, 2023)
Since the end of the Second World War, the political parties associated with the radical right ideology have experienced a certain rise on four occasions. The rise of the radical right parties during the first three waves was not significant and during such upsurge radical right parties remained on the margins of political systems in democratic societies. However, this situation has completely changed during the fourth wave. Namely, the fourth wave has been marked with a great rise of the radical right parties in democratic societies. Precisely in this wave, the parties that are associated with nativism, nationalism, populism, rigidity, exclusivity, authoritarianism, racism, xenophobia, Euroscepticism and anti-globalism began to achieve great electoral results. The rise of the radical right parties in Europe is from 2 percent of the votes in the parliamentary elections in 1980, through 10 percent in 2000, to almost 20 percent of the votes in the parliamentary elections in 2016 and 2017. Such electoral results made it possible for radical right parties to enter governments as a minor party through governmental coalitions usually led by mainstream right political parties. In addition, the political parties of the radical right in the last decade have managed to obtain a large number of seats in the European Parliament. However, it seems that the greatest success of the radical right parties has come from the other side of the Atlantic. The election of Donald Trump as president of the United States, as well as the election of Jair Bolsonaro as president of Brazil, enabled candidates associated with radical right ideology to have the main role in the governments in these countries. Thus, in the last two decades, radical right parties came out of the margins and began to directly influence governmental policies in the area of migration, foreign policy, European integration, human rights, as well as policies that undermine the rule of law, checks and balances and fair electoral processes. In addition to the direct influence on governmental policies by radical right parties, their indirect influence should not be underestimated. First of all, the rise of the radical right parties have caused mainstream right parties to adopt and promote radical right rhetoric and policies. In that direction, leaders of mainstream right parties in Europe (Angela Merkel, Nicolas Sarkozy and David Cameron) have repeatedly publicly declared that the idea of multiculturalism has been dead. It was under David Cameron and the Conservative Party that the Brexit referendum was actualized and implemented. EU enlargement policies were put on hold precisely under the influence of leaders from mainstream right parties. In fact, political positions and values that up to two decades ago would have been political suicide are now openly advocated by radical right political parties, but also by the moderate right parties. Such positions are advocated because radical right frames and issues have become mainstreamed and normalized. In addition to politics, radical right frames and issues are present and advocated by traditional media, social media, civil society groups etc. The so-called transmission actors in public life have contributed to mainstreaming and normalizing radical right values and policies. That is how we have ended up in a situation where it is politically correct and acceptable to promote nationalism, racism, xenophobia, conspiracy theories, authoritarianism, strong-hand leaders, polarization, dichotomies, and the idea that western societies have gone too far with human rights and freedom. It is about a new model of democracy that represents only the bare rule of the majority without taking into account the liberal elements. Elements that actually have contributed democracy to be seen as the best form of government. Elements without which democracy becomes a bad form of government.